Anomaly inflow methods for SCFT constructions in type IIB - Bah, I; Bonetti, F; Minasian, R; Weck, P (Scuola Internazionale Superiore di Studi Avanzati, 2021)
We extend the anomaly inflow methods developed in M-theory to SCFTs engineered via D3-branes in type IIB. We show that the ’t Hooft anomalies of such SCFTs can be computed systematically from their geometric definition. Our procedure is tested in several 4d examples and applied to 2d theories obtained by wrapping D3-branes on a Riemann surface. In particular, we show how to analyze half-BPS regular punctures for 4d N = 4 SYM on a Riemann surface. We discuss generalizations of this formalism to type IIB configurations with F3, H3 fluxes, as well as to F-theory setups.